Risiko kelahiran pramatang spontan di Wad materniti, Hospital Kuala Lumpur - Faisal M.,; Kamarul A.,; Koh G.T.,; Norasmah A.M.,; Norazlina A.A.,; Nor Hisham M.,; Rozita M.,; Salmi R.,; Wan Azlan W.O., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1998)
A case control study was conducted to assess the risk factors for spontaneous preterm birth among births delivered between 1st to 30th September 1994 in Kuala Lumpur Hospital. The risk factors studied were maternal age, maternal weight, parity, sex of the infant, history of antepartum haemorrhage, and history of abortion. A total of 84 cases of spontaneous preterm birth were chosen by quota sampling from the matenity records. Controls were full term births matched by ethnicity. The results showed the significant risk factors of preterm birth are maternal weight (odd ratio 2.8, 95% confidence interval 1.1-7.1) and history of antepartum haemorrhage (odd ratio3.6, 95% confidence interval 1.4-9.4). The association of other risk factors such as maternal age, parity, sex of the infant and history of abortion with spontaneous preterm birth were not statistically significant in this study.